Antifungal activity of Moringa oleifera-based nanoemulsions against Botrytis cinerea in tomato - Ahmad, Khairulmazmi; Ismail, Siti Izera; Omar, Dzolkifli; Ahmadu, Tijjani; Kutawa, Abdulaziz Bashir (Elsevier, 2024)
Control of plant diseases using a plant source is considered an essential and ecofriendly form of disease control. Medicinal plants like Moringa oleifera comprise different chemical constituents that provide a source of biological and new active molecules with antifungal efficacies (Das et al., 2010; Gurjar et al., 2012). Notwithstanding, there are partial reports about the crucial aspects of plant extract formulation and elucidation of their efficacy. Recently, nanoemulsion formulations have been prepared and their efficacy has been validated from such medicinal plants that include copaiba (Copaifera duckei) (Da et al., 2014), oleoresin, Opuntia ficus-indica (Ribeiro et al., 2015), rotenone from Derris elliptica (Asib et al., 2015), eucalyptus oil (Sugumar et al., 2014), Feronia elephantum (Veerakumar et al., 2014), and plai (Zingiber cassumunar Roxb.) (Surassmo et al., 2013). Nanoemulsions have some broad applications, such as in cosmetic, food, and pharmaceutical industries (Solans et al., 2005), as well as in the management of pests and diseases (Wang et al., 2007; Ziedan et al., 2022). The essence of quality control of products (pesticide) is to ensure that some effective and consistent products reach the farm from the agrochemical industry. Quality control, product registration, and product development are dependent on the characterization, profiling, and quantifying of different actives and other constituents in the formulation, which includes degradation and impurities. The study of new biopesticides is dependent on the evaluation of the formulation prepared by the incorporation of plant extracts having antifungal properties. The objective of this study was to characterize nanoemulsion formulations prepared from M. oleifera crude extracts and evaluate their fungicidal activity (in vitro) against Botrytis cinerea representative isolate (BCH07) that has been observed to be highly virulent based on the pathogenicity assay.